A Comparative Study of the Effects of Adrenoceptor Antagonists on Platelet Aggregation and Thromboxane Generation - Greer, I A; Walker, J J; McLaren, M; Calder, A A; Forbes, C D (Thrombosis and Haemostasis, 1985)
Platelet aggregation and thromboxane A2 have been implicated in the pathogenesis of several forms of vascular disease. The aim of this study was to determine the effect of a wide range of adrenoceptor antagonists on platelet aggregation, and thromboxane A2 production, from normal human platelet rich plasma in vitro. Labetalol, pindolol and propranolol inhibited platelet aggregation to collagen in a dose dependent manner. Increasing the concentration of collagen “shifted” the dose response curve to the right. These 3 drugs also significantly inhibited thromboxane A2 generation in response to collagen but not to arachidonic acid. This effect was independent of any inhibitory effect of these drugs on platelet aggregation, and occurred at a drug concentration close to that obtained in vivo. Atenolol, metoprolol, prazosin and timolol were similarly assessed but had no effect on either platelet aggregation or thromboxane A2 generation. This ability of labetalol, pindolol, and propranolol to inhibit platelet aggregation and thromboxane generation, may be of clinical benefit in view of the increasing evidence implicating thromboxane A2 in the pathogenesis of vascular disease.
Keywords: Adrenoceptor antagonists; Platelet aggregation; Thromboxane A2